Corporate Bond Market: International Experience and Russian Practice - I. A. Balyuk (Финансы: теория и практика)
The corporate bond market development is integral to increase the resilience of the Russian economy to external shocks and to build a new growth model in terms of sanctions. The purpose of the article is to analyze the current state of the Russian corporate bond market and to develop proposals for accelerating its further development considering the international experience. The proposals are based on a study of the legal base for the functioning of the international bond market, as well as modern technologies and tools that have proven to be effective in practice. As part of a comparative analysis, a hypothetical-deductive research method has been used. The author has proposed: to develop and adopt independent federal law “On Corporate Bonds”; to amend and supplement the Russian legislation on the protection of the rights of investors who purchase corporate bonds; to make trial (debut) issues in the Russian stock market for bonds denominated in foreign currencies (for example, in RMB); to expand the line of bond types, etc. It has been concluded that, despite the unfavorable external and internal conditions, there is a steady increase in the number of issuers and corporate bonds in circulation in Russia. Active bond issue in the Russian financial market in the near future will happen not only in the corporate, but also in the public segment. It will require more active involvement of individuals in purchasing government and corporate bonds as investors. Various types of institutional investors competing with banks will also be attracted. Corporate bond issue can ease the financial burden of banks and companies that have problems with refinancing their external debts. It can also help to solve the problem of financing of the Russian companies that have focused on obtaining various bank loans in order to implement their business plans. This will help to increase the supply of temporarily free monetary resources, to reduce their cost and more efficiently transform savings into investments.